Exploring the Nexus of Service Learning Initiatives and Quadruple Helix Stakeholders in Malaysia - Sharipah Ruzaina, Syed Aris; Rafeah, Wahi; Ani Mazlina Dewi, Mohamed; Zulinda Ayu, Zulkipli; Rosna, Awang Hashim; Rene II Mediana, Babiera (AMER & cE-Bs by e-International Publishing House, Ltd., UK., 2024)
This paper explores the dynamics of Service Learning Malaysia (SULAM) initiatives and their impact on quadruple helix stakeholders. A qualitative approach involved interviews with 11 lecturers and 16 community participants and thematic analysis to understand how SULAM initiatives impact the stakeholders within the SULAM ecosystem. Findings indicated that the nexus of service-learning initiatives and the stakeholders includes five main themes: University-Industry Collaboration, Government-Academia Partnership, Community Engagement and Empowerment, Skill Development and Human Capital, and Socio-economic Impact. The findings also highlighted the importance of equal partnership among stakeholders to ensure the sustainability of SULAM initiatives.